2015
DOI: 10.15226/2374-6904/2/3/00132
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Foot Morphology and Dynamic Balance Performance as Measured by the Star Excursion Balance Test

Abstract: Open AccessResearch Article neuromuscular control [4]. The protocol is easily implemented in the field and clinic, requiring no specialized equipment or advanced training. In addition, the SEBT is challenging enough to stress the postural control system, making it an ideal task to be used by athletic trainers and physical therapists to assess balance within athletic populations [3,5].The association between dynamic balance, as measured by the SEBT, and foot morphology was investigated in 2 studies with mixed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Lubetzky and Kramer [17], on evaluating the association of various foot morphologies and dynamic balance, concluded that persons with decreased medial longitudinal arch height could reach farther in all directions except the anterolateral direction while performing SEBT, and there were no such balance deficits noted. Similarly, when measuring the effect of various foot postures on static and dynamic balance, Cote et al [20] stated that there was no difference in static balance for pronated or supinated feet compared with control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lubetzky and Kramer [17], on evaluating the association of various foot morphologies and dynamic balance, concluded that persons with decreased medial longitudinal arch height could reach farther in all directions except the anterolateral direction while performing SEBT, and there were no such balance deficits noted. Similarly, when measuring the effect of various foot postures on static and dynamic balance, Cote et al [20] stated that there was no difference in static balance for pronated or supinated feet compared with control.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, when measuring the effect of various foot postures on static and dynamic balance, Cote et al [20] stated that there was no difference in static balance for pronated or supinated feet compared with control. So, it was hypothetically proven that the increase of dynamic balance with increased mechanical support of the medial aspect of a foot possibly resulted from improved sensory receptor activity and neuromuscular function [17,20]. Similarly, a study exploring the influence of foot hyper-pronation and pelvis mechanics in standing position concluded that individuals with hyper-pronated foot presented greater anterior pelvic tilt angle compared with those with neutral foot position [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation